(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Drowning is a form of asphyxia caused by fluid aspiration into air-passages. Hemorrhage in the middle ear, a narrow air filled space, is a recognized result of drowning. The study aims to determine the prevalence of middle ear and mastoid air cell hemorrhage in deaths due to drowning, helping to understand their significance. A cross-sectional autopsy-based study was conducted at B. J. Medical College, Civil Hospital, Ahmedabad, involving 100 cases with alleged drowning histories. Data was collected from medico-legal autopsies and narrated by police and relatives.Middle ear hemorrhage was seen in 65% of cases, out of which it was bilateral in 27% of cases, only right side in 22% of cases, and only left side in 16% of cases. Hemorrhage in mastoid air cells was seen in 57% of cases, out of which it was bilateral in 14% of cases, only the right side in 22% of cases, and only the left side in 21% of cases. Middle ear hemorrhage in drowning cases aids forensic pathologists in determining cause of death, distinguishing drowning from other causes and providing insights into water asphyxiation mechanisms.